HPV E6/E7 mRNA Testing Is More Specific than Cytology in Post-Colposcopy Follow-Up of Women with Negative Cervical Biopsy - Sørbye, Sveinung Wergeland; Arbyn, Marc; Fismen, Silje; Gutteberg, Tore Jarl; Mortensen, Elin Synnøve (PLoS ONE, 2011)
In Norway, women with negative or low-grade cervical biopsies (normal/CIN1) are followed up after six months in order to decide on further follow-up or recall for screening at three-year intervals. A high specificity and positive predictive value (PPV) of the triage test is important to avoid unnecessary diagnostic and therapeutic procedures whereas a low risk of high-grade disease among triage negative women assures safety. At the University Hospital of North Norway, cytology and the HPV mRNA test PreTect HPV-Proofer, detecting E6/E7 mRNA from HPV types 16, 18, 31, 33 and 45, are used in post-colposcopy follow-up of women with negative or low-grade biopsy. In this study, women with negative biopsy after high grade cytology (ASC-H/HSIL) and/or positive HPV mRNA test in the period 2005–2009 were included (n = 520). Histologically confirmed cervical intraepithelial neoplasia of grade 2 or worse (CIN2+) was used as study endpoint. Of 520 women with negative or low-grade biopsy, 124 women (23.8%) had CIN2+ in follow-up biopsy. The sensitivity and specificity of the HPV mRNA test were 89.1% (95% CI, 80.1–98.1) and 92.5% (95% CI, 88.2–96.7), respectively. The ratios of sensitivity, specificity and PPV of HPV mRNA testing compared to repeat cytology for finding CIN2+ was 1.05 (95% CI: 0.92–1.21), 1.21 (95% CI: 1.12–1.32), and 1.49 (95% CI: 1.20–1.86), respectively. The PPV of mRNA was 77.3% (95% CI, 59.8–94.8) in women aged 40 or older. Women with negative cervical biopsy require follow-up before resumption of routine screening. Postcolposcopy HPV mRNA testing was as sensitive but more specific than post-colposcopy cytology. In addition, the HPV mRNA test showed higher PPV. A positive mRNA test post-colposcopy could justify treatment in women above 40 years.